EDUCATION AND DEVELOPMENT OF KEY AND LANGUAGE SKILLS IN TEACHING ACCORDING TO THE METHOD OF TEACHING RUSSIAN LITERATURE IN NATIONAL UNIVERSITY GROUPS - Rakhimova Dilrabo Pulatovna (American Journals, 2022)
The article deals with the development of key and language skills of students of higher educational institutions and the use of certain types of innovative technologies in the classroom according to the methodology of teaching Russian literature.
Keywords: pedagogical process, key skills, language skills, innovative technologies